Development of Manipulative Movement Learning Through Elementary School Level Play Approach - Mahendra, Agung; Lanos, Muhsana El Cintami; Imansyah, Farizal (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
In this research, the development of basic manupulative motion learning will be carried out through a game approach designed using learning principles starting from movement with easy elements to the most difficult. The development of maipulative basic motion learning will be developed with 4 manipulative basic motion models using simple tools that are easily available with a level of security that suits the characteristics of elementary school children. Basic manipulative motion learning will be developed through a play approach expected to provide a good stimulus for children's development in order to master motion well with fun learning. The development of basic manipulative motion learning through a play approach will be outlined in the form of a monograph book of research results as a source of learning and reference for schools. This development product will be tested by adopting the development and research of borg and gall with 4 stages only according to research needs. The objectives of the study are 1) Developing manipulative basic motion learning through an approach to playing at the elementary school level. It is hoped that this development can be implemented at the education unit level and can even be used in society in general to learn basic manipulative movements more enjoyably.